Physiotherapeutic resources used to prevent falls in the elderly population (Research, Society and Development, 2020)
Introduction: Aging is inevitable for every human being, and can cause loss of the body's ability to adapt to situations of physical stress that can be affected in falls tests. Objective: to identify, through an updated bibliographic survey, these resources for the prevention of falls of these patients. Methodology: An integrative literature review was conducted through a search in the databases of the Electronic Scientific Online Library (SCIELO) and Latin American and Caribbean Literature in Health Sciences (LILACS). The inclusion requests used were: experimental articles, written in Portuguese and English, published between 2007 and 2019; available in full free of charge in online collection. Incomplete articles of articles related to another area of health and incomplete, integrative, systematic, bibliographic or meta-analysis reviews were excluded. Results and Discussion: 52 articles were constituted in the research, 44 were excluded and 8 were selected for a research sample. It was observed that balance training, therapeutic exercises that involve kinesiotherapy and hydrokinesiotherapy, proprioceptive and functional training are those that suffer the risk of falls in the elderly. Conclusion: the prevention of falls in the elderly is essential to prevent harmful medical effects. Physiotherapy is an important ally in reducing the risk of falls for these isolates.